Using Social Network Analysis to Compare Vietnamese and Expatriate Teachers' Interactions within Vietnam’s Growing International Schools (Journal of Contemporary Educational Policies and Practices, 2023)
Vietnam’s embrace of globalization and rise in wealth among locals has meant a greater demand for international schools. The growth of the international school sector has resulted in a new kind of international school that serves local Vietnamese students taught by expatriate and Vietnamese teachers. These teachers may have limited interactions due to language and cultural differences. Using a survey, the researchers collected data from the teaching staff at the international school. We analyzed the social networks of Vietnamese and expatriate teachers to identify informal leaders, identify subgroups, compare network density among expatriates and Vietnamese, and test the hypothesis that there is stratification between expatriate and Vietnamese teachers. The findings indicate that Vietnamese and expatriate teachers were not stratified into different subgroups; stratification did occur based on culture. Higher density among Vietnamese teachers suggests more interactions with each other. Implications for this study is that administrators need to build social capital among teachers through professional learning communities. Administrators must also provide teachers with professional development to increase their cultural competency.